The Influence of Discipline, Loyalty and Leadership on Work Productivity at the Secretariat of the Regional People's Representative Council of Selayar Islands Regency - Lidya Ariani (Yayasan Amerta Insan Unggul, 2023)
This study aims to examine the influence of discipline, loyalty and leadership on work productivity at the Secretariat of the Regional People's Representative Council of the Selayar Islands Regency. This study uses primary data sources in which researchers conduct research by distributing questionnaires to 94 respondents at the Secretariat of the Regional House of Representatives of the Selayar Islands Regency. The results of the study show that there is a positive and significant influence of discipline, loyalty and leadership on work productivity. This is evidenced by the results of the test carried out by the t test by looking at the significant value of t count of 0.000 < from the significant level (0.000 < 0.05). Based on the results of the t test that has been carried out on the discipline variable (X1) on work productivity (Y) a value of 0.048 < 0.05 is obtained, besides that it is known that the significant value of X1 to Y is 0.250. Based on the results of the t-test that has been carried out on the loyalty variable (X2) on work productivity (Y) the value is 0.039 <0.05, besides that it is known that the significant value of X2 to Y is 0.313. And the results of the t test that has been carried out on the leadership variable (X3) on work productivity (Y) obtained a value of 0.000 <0.05 besides that it is known that the significant value of X3 to Y is 0.487. So it can be concluded that the variables of discipline, loyalty and leadership have a positive and significant effect on work productivity at the Secretariat of the Regional People's Representative Council of the Selayar Islands Regency.